1996
DOI: 10.1093/oxfordjournals.eurheartj.a015046
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac anatomy, function and metabolism in elite cyclists assessed by magnetic resonance imaging and spectroscopy

Abstract: We investigated whether left ventricular hypertrophy in elite cyclists is associated with functional changes or abnormal energy metabolism. Left ventricular hypertrophy is a powerful risk factor for sudden cardiac death with different prognostic significance among the various geometric forms. Cyclists may have a combination of mixed eccentric and concentric hypertrophy. Magnetic resonance imaging was used to define left ventricular mass, geometry and function. Thirteen highly trained male cyclists and 12 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
1
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 35 publications
3
18
1
2
Order By: Relevance
“…In addition, we found a similar decrease in myocardial PCr/ATP ratio during high workloads caused by atropine-dobutamine stress in cyclists and sedentary control subjects. This study extends our previous findings in cyclists, 17 in whom we demonstrated a Figure 2. Representative cardiac 31 P magnetic resonance spectroscopy spectra of a cyclist and a control subject at rest and during atropine-dobutamine stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we found a similar decrease in myocardial PCr/ATP ratio during high workloads caused by atropine-dobutamine stress in cyclists and sedentary control subjects. This study extends our previous findings in cyclists, 17 in whom we demonstrated a Figure 2. Representative cardiac 31 P magnetic resonance spectroscopy spectra of a cyclist and a control subject at rest and during atropine-dobutamine stress.…”
Section: Discussionsupporting
confidence: 92%
“…14 -16 A recent study from our institution demonstrated normal systolic function parameters and a normal high-energy phosphate metabolism in elite cyclists at rest. 17 In that study, however, we did not investigate diastolic function or high-energy phosphate metabolism during stress. Because abnormalities of diastolic filling may precede abnormalities of systolic function in the early stages of disease, we considered it important to evaluate diastolic function in cyclists as well.…”
mentioning
confidence: 97%
“…This type of LVH is considered physiological [5][6][7][8][9][10]. Conditions like hypertensive heart disease lead to pathological LVH [11][12][13][14][15], as it is often associated with perivascular and interstitial fibrosis of left ventricular myocardium [16], diastolic heart failure [17,18], arrhythmias [19,20] and mortality [21].Previous studies from our institution have already addressed the issue of physiological versus pathological LVH [5,22,23]. First of all we studied the accuracy of M-mode echocardiography and two different twodimensional echocardiographic approaches in the assessment of left ventricular mass and volumes in endurance-trained and strength-trained athletes, using cardiovascular magnetic resonance (CMR) imaging as reference standard [23].…”
mentioning
confidence: 99%
“…Previous studies from our institution have already addressed the issue of physiological versus pathological LVH [5,22,23]. First of all we studied the accuracy of M-mode echocardiography and two different twodimensional echocardiographic approaches in the assessment of left ventricular mass and volumes in endurance-trained and strength-trained athletes, using cardiovascular magnetic resonance (CMR) imaging as reference standard [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation